Mild and severe salt stress responses are age-dependently regulated by abscisic acid in tomato - Holsteens, Kristof; De Jaegere, Isabel; Wynants, Arne; Prinsen, Els L. J.; Van de Poel, Bram (Frontiers in Plant Science, 2022)
Salt stress hampers plant growth and development through both osmotic and ionic imbalances. One of the key players in modulating physiological responses towards salinity is the plant hormone abscisic acid (ABA). How plants cope with salinity largely depends on the magnitude of the soil salt content (stress severity), but also on age-related developmental (ontogeny). Here we studied how ABA directs salt stress responses in tomato plants for both mild and severe salt stress in leaves of different ages. We used the ABA-deficient mutant notabilis, which contains a null-mutation in the gene of a rate-limiting ABA biosynthesis enzyme 9-cis-epoxycarotenoid dioxygenase (NCED1), leading to impaired stomatal closure. We showed that both old and young leaves of notabilis plants keep a steady-state transpiration and photosynthesis rate during salt stress, probably due to their dysfunctional stomatal closure. At the whole plant level, transpiration declined similar to the wild-type, impacting final growth. Notabilis leaves were able to produce osmolytes and accumulate ions in a similar way as wild-type plants, but accumulated more proline, indicating that osmotic responses were not impaired by the NCED1 mutation. Besides NCED1, also NCED2 and NCED6 are strongly upregulated under salt stress, which could explain why the notabilis mutant did not show a lower ABA content upon salt stress, except in young leaves. This might be indicative of a salt-mediated feedback mechanism on NCED2/6 in notabilis and might explain why notabilis plants seem to perform better under salt stress compared to wild-type plants with respect to biomass and water content accumulation.